TRANSLATION THEORY OF LITERARY TEXTS - Xudoymuratova Kurbonoy (Zeta Repository, 2023)
The artistic image is one of the key concepts in those areas of literary criticism that proceed from the aesthetic nature of art. Meanwhile, in the definition and application of the concept, there is a lot of obscure, debatable. A literary work appears to the reader as a text, in a linear sequence of linguistic signs, but images appear behind words, sentences - why? always? what are the criteria for their selection? This range of issues is discussed in this article. But first, let us recall the provisions that, apparently, can be considered generally accepted in the theory of the image.